2003
DOI: 10.1074/jbc.m208438200
|View full text |Cite
|
Sign up to set email alerts
|

The Direct Interaction of Phospholipase C-γ1 with Phospholipase D2 Is Important for Epidermal Growth Factor Signaling

Abstract: The epidermal growth factor (EGF) receptor has an important role in cellular proliferation, and the enzymatic activity of phospholipase C (PLC)-␥1 is regarded to be critical for EGF-induced mitogenesis. In this study, we report for the first time a phospholipase complex composed of PLC-␥1 and phospholipase D2 (PLD2). PLC-␥1 is co-immunoprecipitated with PLD2 in COS-7 cells. The results of in vitro binding analysis and coimmunoprecipitation analysis in COS-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…Molecular analysis of the interaction between endogenous Grb2 and PLD2 mutants revealed that (Xu et al, 2001), whereas residue Y 179 is conserved only in the PX domain of mammalian PLDs. The N-terminal region of PLD2, containing the PX (a.a. and domains, is the most representative region involved in PLD2 protein-protein interactions (Park et al, 2000;Kim et al, 2002;Ahn et al, 2003;Jang et al, 2003). The relevance of the PX domain is illustrated by the fact that its deletion from PLD2 produces a catalytically inactive enzyme in vitro (Sung et al, 1999;Park et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analysis of the interaction between endogenous Grb2 and PLD2 mutants revealed that (Xu et al, 2001), whereas residue Y 179 is conserved only in the PX domain of mammalian PLDs. The N-terminal region of PLD2, containing the PX (a.a. and domains, is the most representative region involved in PLD2 protein-protein interactions (Park et al, 2000;Kim et al, 2002;Ahn et al, 2003;Jang et al, 2003). The relevance of the PX domain is illustrated by the fact that its deletion from PLD2 produces a catalytically inactive enzyme in vitro (Sung et al, 1999;Park et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the extra five residues in γ and δ isoforms (splice site 2) occur within a region that is variable in other PX domains. This insertion aligns within the "PXXP" motif of p47 phox and PLD1, which is exposed and can engage in either intramolecular or intermolecular protein-protein interactions [34,38]. Several other proteins contain PX domains that lack this proline-rich motif entirely [27].…”
Section: Alternative Splicing Of Noxo1 and Its Effects On Px Domain Smentioning
confidence: 99%
“…PX domains are found in a range of proteins associated with membranes such as PLD, sorting nexins and yeast Vam7p, and contain a proline-rich motif, which enables them to recognize the Src homology 3 (SH3) domain (Jang et al, 2003;Kay et al, 2000;Ponting, 1996). Moreover, recent studies have shown that, specific interactions between PX domains and phosphoinositides play a crucial role in the localization and enzymatic regulation of PX-domaincontaining proteins, and have identified the PX domain as a phosphoinositide-binding module involved in cellular signal transduction Cheever et al, 2001;Ellson et al, 2001;Kanai et al, 2001;Xu et al, 2001;Zhan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%